Intellectual Property Right on Basmati Rice: Current Scenario and Evidences of Origin, Diversity, Cultivation and Use Values of Basmati Rice in Nepal - Joshi, Bal Krishna; Ghimire, Krishna Hari; Bista, Prakash Raj; Yadaw, Ram Baran; Shrestha, Ram Krishna; Kharel, Gaurish Krishna; Paneru, Prakash; KC, Ram Bahadur; Bhandari, Deepak (Nepal Journal of Biotechnology, 2021)
Basmati rice, also called the king/prince of rice landraces has very special values in Nepalese society as well as in other countries of Indian Subcontinent. With the objectives of collecting, analyzing and documenting Basmati related information in Nepal, we visited different sites; carried out key informant surveys; organized focus group discussions, online interaction and discussion meetings; requested all relevant offices/ persons/ stakeholders through phone, website, and letter to share information; organized high level official meeting, and Basmati rice expert meeting; documented video documentary and did online as well as library search. Because of its high market value at global level, many countries and organizations have been attempting to get intellectual property rights (mainly patent and geographical indication tag) on Basmati rice. India applied for GI tag to Basmati rice in the European Union (EU) in July 2018, and Nepal submitted opposition letter along with proofs and evidences of origin, diversity, cultivation and use values of Basmati rice on 9 December 2020. A total 133 Basmati type rice landraces are grown in 60 districts of Nepal. Basmati rice is traditionally grown, sold, and consumed in geographically localized areas of Nepal since ancient time. International and national scientists have defined lower altitude of Nepal as one of the centers of origin of Basmati rice. Many Nepalese basmati rice landraces have been characterized and evaluated using morphological traits, isozymes and DNA markers. Four basmati type of rice landraces have been registered in National Seed Board. Many community seed banks have maintained different types of Basmati rice landraces. National Agriculture Genetic Resources Center and International genebanks have collected more than 80 and conserved 68 basmati landraces. Basmati rice landraces have geo-linked traits. The historical culture of production, consumption and marketing of native basmati rice in Nepal should always be favored by both national and international rules and regulations. Nepal has ample and valid evidences to get geographical indication (GI) right on Basmati rice.